Print Culture and Local Islamic Identity in West Java: Qurâ€™Änic Commentaries in Sundanese Islamic Magazines (1930-2015) - Rohmana, Jajang A; Zuldin, Muhamad (AL-TAHRIR, 2019)
Abstract: This article focuses on the construction of Islam-Sunda identity in West Java which is reflected in the rubric of the qurâ€™Änic commentary or tafsÄ«r in the Sundanese print media. My object matter is six Sundanese Islamic magazines published between 1930-2015, i.e. Tjahja Islam, Al-Imtisal, Al-Mawa'idz, Almoechtar, Iber and Bina Daâ€™wah using the analysis of identity construction. Although Sundanese Muslims devided into traditionalist and modernist, I confirm that all Sundanese Islamic magazines show the local Islamic identity which is called as Islam-Sunda. The identity of Islam-Sunda in the magazine rubric of qurâ€™Änic commentary can be seen at following aspects: the interpretation of surahs which have an important role in Sundanese daily life, the interpretation of Islamic stories, the use of Sundanese phrases that touch their hearts, the formation of a pious Sundanese personality and the involvement of Islamic scholars or ajengan as an exegete of the Qurâ€™Än. This study asserts that the magazine rubric of qurâ€™Än commentary is not only have a lot of Islamic messages, but also to be an expression of Islamic identity in Sundanese print media.Ø§Ù„Ù…Ù„Ø®Øµ: ØªØ±ÙƒØ² Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ø¹Ù„Ù‰ Ø¨Ù†Ø§Ø¡ Ø§Ù„Ù‡ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø³ÙˆÙ†Ø¯Ø§ÙˆÙŠØ© ÙÙŠ Ø¬Ø§ÙˆØ© Ø§Ù„ØºØ±Ø¨ÙŠØ© Ø§Ù„ØªÙŠ ØªÙ†Ø¹ÙƒØ³ ÙÙŠ Ø¹Ù†Ø§ÙˆÙŠÙ† Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ù‚Ø±Ø¢Ù† Ø¹Ù† ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ø¥Ø¹Ù„Ø§Ù… Ø§Ù„Ù…Ø·Ø¨ÙˆØ¹Ø© Ø§Ù„Ø³ÙˆÙ†Ø¯Ø§ÙˆÙŠØ©. ÙˆØ§Ù„Ù…ÙˆØ¶ÙˆØ¹ Ù…Ù† Ø°Ù„Ùƒ Ù‡Ùˆ Ø³ØªØ© Ù…Ø¬Ù„Ø§Øª Ø§Ù„Ø³ÙˆÙ†Ø¯Ø§ÙˆÙŠØ© Ù†ÙØ´Ø±Øª Ù…Ù† Ø®Ù„Ø§Ù„ Ø³Ù†Ø© Ù¡Ù©Ù£Ù -Ù¢Ù Ù¡Ù¥ØŒ ÙˆÙ‡ÙŠ: Ø³ØÙŠØ§ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… (Cahya Islam)ØŒ ÙˆØ§Ù„Ø§Ù…ØªØ«Ø§Ù„ (al-Imtisal)ØŒ ÙˆØ§Ù„Ù…ÙˆØ§Ø¹Ø¸ (Al-Mawaâ€™idz)ØŒ ÙˆØ§Ù„Ù…Ø®ØªØ§Ø± (Almoechtar)ØŒ ÙˆØ¥ÙŠØ¨ÙŠØ± (Iber)ØŒ ÙˆØ¨ÙŠÙ†Ø§ Ø¯Ø¹ÙˆØ© (Bina Daâ€™wah). ÙÙ…Ù† Ø®Ù„Ø§Ù„ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨Ù†Ø§Ø¡ Ø§Ù„Ù‡ÙˆÙŠØ©, Ø£ÙƒØ¯ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø£Ù†Ù‡ Ø¹Ù„Ù‰ Ø§Ù„Ø±ØºÙ… Ù…Ù† ÙˆØ¬ÙˆØ¯ ØªÙ†ÙˆØ¹ ÙÙŠ Ø§Ù„Ø¯ÙŠØ§Ù†Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙÙŠ Ø¬Ø§ÙˆØ© Ø§Ù„ØºØ±Ø¨ÙŠØ©ØŒ Ø¨ÙŠÙ† Ø§Ù„ØªÙ‚Ù„ÙŠØ¯ÙŠÙŠÙ† ÙˆØ§Ù„ØØ¯Ø§Ø«ÙŠÙŠÙ†ØŒ Ø¥Ù„Ø§ Ø£Ù†Ù‡Ø§ Ø¬Ù…ÙŠØ¹Ù‹Ø§ ØªØ¸Ù‡Ø± Ø¹Ù„Ù‰ Ù†ÙØ³ Ø§Ù„Ù‡ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ù…ØÙ„ÙŠØ©. ÙˆØªÙ„Ùƒ Ø§Ù„Ù‡ÙˆÙŠØ© ØªØ¸Ù‡Ø± ÙÙŠ Ø¹Ù†Ø§ÙˆÙŠÙ† Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ù‚Ø±Ø£Ù† Ø¹Ù† Ø§Ù„Ù…Ø¬Ù„Ø§Øª, Ù…Ø«Ù„: Ø§Ù„ØªØ¹Ø±ÙŠØ¶ ØªÙØ§Ø³ÙŠØ±Ø§Ù„Ø³ÙˆØ±Ø© Ø§Ù„ÙˆØ¸ÙŠÙÙŠØ© ÙÙŠ Ø§Ù„ØÙŠØ§Ø© Ø§Ù„ÙŠÙˆÙ…ÙŠØ© Ø§Ù„Ø³ÙˆÙ†Ø¯Ø§ÙˆÙŠØ©ØŒ ÙˆØªÙØ³ÙŠØ± Ø§Ù„Ø§ÙŠØ© Ø¹Ù† Ø§Ù„Ù‚ØµØµ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©ØŒ ÙˆØ§Ø³ØªØ¹Ù…Ø§Ù„ Ø§Ù„Ø¹Ø¨Ø§Ø±Ø© Ø§Ù„Ø³ÙˆÙ†Ø¯Ø§ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØªÙŠ ØªØªØ£Ø«Ø± Ø§Ù„Ù‰ Ø§Ù„Ù‚Ù„Ø¨ØŒ ÙˆÙ…Ù‡Ù…Ø© ØªØ´ÙƒÙŠÙ„ Ø§Ù„Ø´Ø®ØµÙŠØ© Ø§Ù„Ø³ÙˆÙ†Ø¯Ø§ÙˆÙŠØ© Ø§Ù„ØµØ§Ù„ØØ©, ÙˆØ¥Ø´ØªØ±Ø§Ùƒ Ø§Ø¬Ø§Ù†Ø¬Ø§Ù† (ajengan) ÙƒØ§Ù„Ù…ÙØ³Ø±. ÙˆØªØ¯Ù„ Ù‡Ø¯Ù‡ Ø¹Ù„Ù‰ Ø£Ù† Ø¹Ù†Ø§ÙˆÙŠÙ† Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ù‚Ø±Ø£Ù† ÙÙŠ Ø§Ù„Ù…Ø¬Ù„Ø§Øª Ù„Ø§ ØªÙ…Ù„Ø£ Ø¨Ø§Ù„Ø±Ø³Ø§Ø¦Ù„ Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© ÙØØ³Ø¨ØŒ Ø¨Ù„ Ø£Ù†Ù‡ ÙƒØ¬Ø²Ø¡ Ù…Ù† Ø§Ù„ØªØ¹Ø¨ÙŠØ± Ø¹Ù† Ø§Ù„Ù‡ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø³ÙˆÙ†Ø¯Ø§ÙˆÙŠØ© ÙÙŠ ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ø¥Ø¹Ù„Ø§Ù… Ø§Ù„Ù…Ø·Ø¨ÙˆØ¹Ø©.Abstrak: Artikel ini memfokuskan pada masalah konstruksi identitas Islam Sunda di Jawa Barat yang tercermin dalam rubrik tafsir Al-Qurâ€™an di media cetak Sunda. Objeknya adalah enam majalah Sunda yang terbit antara tahun 1930-2015, yakni Tjahja Islam, Al-Imtisal, Al-Mawaâ€™idz, Almoechtar, Iber dan Bina Daâ€™wah. Melalui analisis konstruksi identitas, kajian ini menegaskan bahwa meski terdapat ragam keberagamaan Islam di Jawa Barat, antara tradisionalis dan modernis, tetapi semua menunjukkan identitas Islam lokal yang hampir sama, yakni konstruksi identitas Islam. Dalam rubrik tafsir Al-Qurâ€™an, identitas tersebut bisa dilihat dalam sajian penafsiran surah-surah yang sangat fungsional dalam keseharian orang Sunda, tafsir kisah-kisah Islami, penggunaan ungkapan Sunda Islami yang mengena dalam hati, misi pembentukan pribadi Sunda yang saleh dan keterlibatan ajengan sebagai mufasir. Hal ini menunjukkan bahwa rubrik tafsir di majalah tidak hanya sarat dengan pesan keagamaan, tetapi juga menjadi bagian dari ekspresi identitas Islam Sunda dalam media cetak.